Μελέτη ευστάθειας στην επιλογή επενδυτικών σχεδίων με πολυκριτηριακό προγραμματισμό λαμβάνοντας υπόψη και την εταιρική περιβαλλοντική ευθύνη - Κανέλλος, Γεώργιος (Εθνικό Μετσόβιο Πολυτεχνείο. Σχολή Ηλεκτρολόγων Μηχανικών και Μηχανικών Υπολογιστών. Τομέας Ηλεκτρικών Βιομηχανικών Διατάξεων και Συστημάτων Αποφάσεων, 2014)
An enterprise is a financial unit that uses the factors of production as well as trading operations in order to achieve maximum profit. The achieved profit must in general be greater than the amounts of salary paid for labor. According to this definition it becomes clear that the financial sector of an enterprise has been the keystone for its growth and success. However, nowadays this traditional approach has been supplemented by the notion that an enterprise must engage in other non-profit seeking activities that have environmental and social merits. This notion is formally expressed through the concept of corporate social responsibility (CSR).